Culturing functional pancreatic islets on α5-laminins and curative transplantation to diabetic mice - Sigmundsson,K; Ojala,JRM; Öhman,MK; Österholm,A-M; Moreno-Moral,A; Domogatskaya,A; Chong,LY; Sun,Y; Chai,X; Steele,JAM; George,B; Patarroyo,M; et al. (Matrix Biology, 2018)
The efficacy of islet transplantation for diabetes treatment suffers from lack of cadaver-derived islets, islet necrosis and long transfer times prior to transplantation. Here, we developed a method for culturing mouse and human islets in vitro on α5-laminins, which are natural components of islet basement membranes. Adhering islets spread to form layers of 1-3 cells in thickness and remained normoxic and functional for at least 7days in culture. In contrast, spherical islets kept in suspension developed hypoxia and central necrosis within 16h. Transplantation of 110-150 mouse islets cultured on α5-laminin-coated polydimethylsiloxane membranes for 3-7days normalized blood glucose already within 3days in mice with streptozotocin-induced diabetes. RNA-sequencing of isolated and cultured mouse islets provided further evidence for the adhesion and spreading achieved with α5-laminin. Our results suggest that use of such in vitro expanded islets may significantly enhance the efficacy of islet transplantation treatment for diabetes.